2010
DOI: 10.1557/proc-1264-bb05-18
|View full text |Cite
|
Sign up to set email alerts
|

Atom Probe Tomography characterization of the microstructural evolution of a low copper reactor pressure vessel steel under neutron irradiation

Abstract: A low copper reactor pressure vessel steel was characterised by atom probe tomography after neutron irradiation at different fluences. The specimens were irradiated within the frame of the Surveillance Program of a production reactor. Roughly spherical clusters enriched in nickel, manganese, silicon and, in a lesser extent, phosphorus and copper were observed at all fluences. The chemical composition of these clusters shows no evolution with fluence, as well as their diameter, close to 3 nm. Their number densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This clearly supports the hypothesis that solute atoms are continuously dragged by single point defects towards point-defect sinks, irrespective of the magnitudes of solute-solute interactions. Next, a large number density (~10 22 m -3 to 10 2 3 m -3 ) of roughly spherical NSRC is systematically reported in nearly all APT studies on irradiated steels [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. A typical image obtained from APT is shown in Fig.…”
Section: Experimental Evidencementioning
confidence: 77%
See 2 more Smart Citations
“…This clearly supports the hypothesis that solute atoms are continuously dragged by single point defects towards point-defect sinks, irrespective of the magnitudes of solute-solute interactions. Next, a large number density (~10 22 m -3 to 10 2 3 m -3 ) of roughly spherical NSRC is systematically reported in nearly all APT studies on irradiated steels [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. A typical image obtained from APT is shown in Fig.…”
Section: Experimental Evidencementioning
confidence: 77%
“…In this view, NSRC formation in RPV steels would essentially be an irradiation-enhanced process. In contrast, other researchers have suggested that the evolution of the system is dominantly driven by mechanisms specific to irradiation [16,21,46,47], i.e. considering as crucial the role of self-interstitial atoms (SIA).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mechanism of the formation of these solute clusters and dislocation loops may be the radiation-induced segregation (RIS) of solutes to point defects clusters. 25,26) The formation of solute clusters and dislocation loops depend on mainly the original shape of point defect clusters.…”
Section: 24)mentioning
confidence: 99%
“…Recent 3DAP observations of surveillance materials have provided key data for understanding microstructural evolution in actual vessel materials under operating conditions. In surveillance specimens (16MND5 steels with 0.09 and 0.044%Cu) irradiated in French PWRs at 2 × 10 11 n/cm 2 /s, fine clusters (3-4 nm in diameter) were detected and the cluster density increased with fluence up to 1.7 × 10 20 n/cm 2 [51,52]. The averaged composition in the 0.044%Cu steel was Fe-6Mn-10Ni-8Si in at% and did not change with fluence up to 7.6 × 10 19 n/cm 2 .…”
Section: Solute Clustersmentioning
confidence: 99%